Adaptation, grain yield and nutritional characteristics of quinoa (Chenopodium quinoa) genotypes in marginal environments of the Aral Sea basin - Khaitov, Botir; Karimov, Aziz A.; Toderich, Kristina; Sultanova, Zulfiya; Mamadrahimov, Azimjon; Allanov, Kholik; Islamov, Sokhib (Journal of Plant Nutrition, 2020)
Climate resilience of the C 3 halophyte Chenopodium quinoa Willd potentiates its production in drought and salt-prone areas. A two-year field experiment was laid out in completely randomized block designs with three replications to test the adaptability of this crop to abiotic stresses, grain yield and nutritional quality in marginal areas of the Aral Sea basin. The vegetation cycle of the investigated five quinoa lines ranged between 107-133 days based on genotype characteristics. Q5 and Q3 lines had early ripening ability of (107 and 113 days), higher seed weight (2.7 and 2.35 g/1000 seeds), better seed germination (68.3 and 56.7%) associated with stress tolerance. All these features reflected in high yield potential of Q5 and Q3 genotypes, exhibiting average grain yields of 2537.8 and 2361.7 kg ha −1 , respectively. The lowest yield was recorded in Q1 with an average yield of 1551.3 kg ha −1 . Nutrition features were similar in the tested quinoa genotypes; however, the highest protein, lignin and lipid contents were recorded in Q5 genotype. Q3 and Q5 genotypes showed higher salinity tolerance than other genotypes when different concentrations (0-500mM) of NaCl and MgSO 4 exposed under laboratory conditions. Implementation of innovative technology in cultivation, harvesting, storage and processing will help incorporate quinoa into the Aral Sea Basin's agricultural development and scale up as an alternate crop for food and feed.